Enthesitis is a clue to the diagnosis of spondyloarthritis, focus on psoriatic arthritis - Ye. D. Yehudina; S. A. Trypolka (Современная ревматология, 2021)
Enthesitis is a common clinical feature of spondyloarthritis (SpA), characterized by inflammation of the tendon or ligament attachment site to a bone or joint capsule. The importance of detecting enthesitis for the diagnosis of SpA is confirmed by its inclusion in the classification criteria for psoriatic arthritis (PsA) – CASPAR – and in the classification criteria for SpA of the international group for the study of spondyloarthritis – ASAS. Enthesitis may be the first clinical sign of SpA, as well as the leading symptom that significantly influences the therapeutic choice. Enthesitis occurs in 30–50% of patients with SpA and is associated with high disease activity, more severe pain and worse quality of life. The frequency of enthesitis detected by ultrasound in patients with PsA is approximately 4 times higher than in patients with ankylosing spondylitis and is associated with the severity of the disease. The review presents current data on the pathophysiology, diagnosis and treatment of enthesitis. Recent studies emphasize the role of imaging methods for the diagnosis of enthesitis due to their higher sensitivity and specificity compared to clinical examination. There is very limited information on the effect of synthetic disease-modifying antirheumatic drugs on enthesitis, while targeted drugs and biologic therapy have shown high efficacy in its treatment compared to placebo. Preliminary evidence suggests that targeting interleukin (IL) 17 or IL12/23 may be more effective in enthesises inflammation suppression than tumor necrosis factor α inhibition.